A sala de aula em filmes: um diálogo entre a docência e o ensino educativo - Sanches, Marcia de Mattos (2012)
This dissertation studies, in seven films, the educators role in the classroom in order to verify whether there is, in pedagogical attitudes of the protagonists, an educational teaching which contributes to widen up the teaching and learning procedures. One of the criteria to choose the use of these films as a textbook was the fact that the teachers have written books about their experiences in school environment or have founded institutions focused on both musical teaching as well as students writing and reading development. The motivation for this study was aroused by the uneasiness in terms of quality of the educational system still ruled by knowledge fragmentation, put into practice in our schools and by the observation of the educational actions which, make the students awaken to knowledge, in opposition to those ones which make them be distant and feel aversion about their studies. With a set of 91 descriptive classes which were used as documentary basis and bibliographical sources, the aim of this study is to present the films as providers of investigations and knowledge. Besides, by apprehending the dynamic of the teaching procedures in the films, the most recurrent themes were came out, and it turned to be possible to verify whether they could show a kind of teaching that is informed and able to rejoin knowledge, at the same time, whether they could consider the human being condition insight. This research is based on Edgar Morin s complexity studies whose theoretical core involve his work: La Tête Bien Faite - Repenser la réforme, réformer and Les sept savoirs nécessaires à l éducation du futur which translation into portuguese has been, respectively: A cabeça bem feita: repensar a reforma, reformar o pensamento e Os sete saberes necessários à educação do futuro, to understand that this theory has brought the importance of teaching in terms of entirety of the challenges and the uncertainties of our era as well.